Formulasi Inokulan Jamur Pembentuk Gubal Gaharu pada Tanaman Ketimunan (Gyrinops versteegii) - I MADE MEGA; DEWA KETUT SUANDA; DESAK NYOMAN KASNIARI; WAYAN SUENA; MADE ADI OKA PARWATA (Fakultas Pertanian Universitas Udayana, 2012)
This study aims to find the most effective formulation of the gaharu agar wood forming fungi inoculantswhich infect Gyrinops versteegii plants, thus producing high quality agar wood. The method used inthis research is the randomized block design (RBD) with three replication. The treatments were twofungi as inoculant applied saperately each and a combination of Rhisopus sp. and Fusarium sp. in theform of solid and liquid. The treatments tested were: (A) Fusarium solani fungi inoculant in solid form,(B) Rhisopus sp.fungi inoculant in solid form, (C) Mixture of Rhisopus sp. and Fusarium solani fungiinoculants in solid form, (D) Fusarium solani fungi inoculant in liquid form, (E) Rhisopus sp.fungiinoculants in liquid form, (F) Mixture of Rhisopus sp. and Fusarium solani fungi inoculants in liquidform, and (G) A combination of solid and liquid of Rhisopus sp. and Fusarium solani fungi inoculants.The parameters measured were the agar wood formed: agar wood fragrance level, color of agar woodand resin content of the agar wood. Furthermore, the data is analyzed statistically by analysis ofvariance. The results showed that, treatments of inoculants formulations significantly affects the aromaand resin content of agar wood. Formula of G (a combination of solid and liquid Rhisopus sp. andFusarium solani fungi inoculants) and F (a combination of liquid Rhisopus sp. and Fusarium solanifungi inoculants) produced agar wood of the highest quality compared to other formulas. Formula Gand F produced each agar wood with black and blackish-brown colour, with strong aroma (fragrance),and a resin content of 7.69% and 6.98%.